Studi Kasus Pola Manajemen Pondok Pesantren Al-Raisiyah di Kota Mataram - Nurul Yakin (Universitas Islam Negeri Mataram, 2014)
Pesantren is the oldest Islamic educational institution in Indonesia. Due to its strongly established existence and dyanamics up to present times, it has become an interesting topic of research. This article attempts to examine one of the traditional pesantrens in Mataram, namely Al-Raisiyah. Using case study method, it focuses the pesantren’s management. This study argues that the pesantren does employ a single management but a multi-management system. The pesantren combines the official curriculum of education unit level with special cirruculum of pesantren. Although the pesantren does not recruit teachers openly so the recruitment is not competitive, it adopts an open and modern management regarding student affairs, infrastructure and financial resources. The pesantren’s school committee, which is very traditional in its vision and orientation, tends to emphasize a model of traditional pattern of social communication and relations.